Math, asked by hyperxman2007, 5 months ago

if x⁴+1/x⁴=2 find x²+1/x²,x+1/x and x³+1/x³ please give line by line explaination​

Answers

Answered by mathdude500
1

Identity Used :-

 \boxed{ \pink{ \bf \:  {(x + y)}^{2} =  {x}^{2} +  {y}^{2} + 2xy}}

 \boxed{ \pink{ \bf \: {(x + y)}^{3} =  {x}^{3} +  {y}^{3} + 3xy(x + y)}}

Solution :-

Given that,

\rm :\longmapsto\: {x}^{4}  + \dfrac{1}{ {x}^{4} }  = 2

Adding 2 on both sides, we get

\rm :\longmapsto\: {x}^{4}  + \dfrac{1}{ {x}^{4} } + 2  = 2 + 2

\rm :\longmapsto\: {x}^{4}  + \dfrac{1}{ {x}^{4} } + 2 \times  {x}^{2} \times \dfrac{1}{ {x}^{2} }    = 4

\rm :\longmapsto\: {\bigg(  {x}^{2} + \dfrac{1}{ {x}^{2} }  \bigg) }^{2}  = 4

 \red{\bf\implies \: {x}^{2} + \dfrac{1}{ {x}^{2} }   = 2}

On adding 2 both sides, we get

 \rm :\longmapsto\:\: {x}^{2} + \dfrac{1}{ {x}^{2} }  + 2  = 2 + 2

 \rm :\longmapsto\:\: {x}^{2} + \dfrac{1}{ {x}^{2} }  + 2 \times x \times  \dfrac{1}{x}   = 4

\rm :\longmapsto\: {\bigg( x + \dfrac{1}{x} \bigg) }^{2}  = 4

 \pink{\bf\implies \:x + \dfrac{1}{x}  =  \pm \: 2}

Now,

We consider first,

\rm :\longmapsto\:x + \dfrac{1}{x}  = 2

On cubing both sides we get

\rm :\longmapsto\: {\bigg(x +  \dfrac{1}{x}  \bigg) }^{3}  = 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  + 3 \times x \times \dfrac{1}{x} \bigg( x + \dfrac{1}{x} \bigg) = 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  + 3 \times 2 = 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  + 6 = 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} } = 8  - 6

 \green{\bf\implies \:\: {x}^{3}  +  \dfrac{1}{ {x}^{3} } = 2}

Now,

We consider second case,

\rm :\longmapsto\:x + \dfrac{1}{x}  = -  2

On cubing both sides, we get

\rm :\longmapsto\: {\bigg(x +  \dfrac{1}{x}  \bigg) }^{3}  =  - 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  + 3 \times x \times \dfrac{1}{x} \bigg( x + \dfrac{1}{x} \bigg) =  - 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  + 3 \times ( - 2) =  - 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }  - 6 =  - 8

\rm :\longmapsto\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }   =  - 8  + 6

 \purple{\bf\implies \:\: {x}^{3}  +  \dfrac{1}{ {x}^{3} }   =  - 2}

 \large{\boxed{ \bf{Additional \:  Information}}}

More Identities to know:

  • (a + b)² = a² + 2ab + b²

  • (a - b)² = a² - 2ab + b²

  • a² - b² = (a + b)(a - b)

  • (a + b)² = (a - b)² + 4ab

  • (a - b)² = (a + b)² - 4ab

  • (a + b)² + (a - b)² = 2(a² + b²)

  • (a + b)³ = a³ + b³ + 3ab(a + b)

  • (a - b)³ = a³ - b³ - 3ab(a - b)

Similar questions